Digital Activism for Peace: Exploring Instagram's Role in Interfaith Dialogue in Indonesia - Wahyuni, Dwi; Karlina, Intan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Social media has transformed Indonesia's social activism landscape, especially in efforts to build peace and interfaith dialogue. This study uses a virtual ethnographic approach to examine how four interfaith communities (JAKATARUB Bandung, PELITA Padang, Eco Bhinneka Kalbar, and Peace Generation Makassar) use Instagram to promote peace and interreligious dialogue. This study analyzes digital content activism strategies, communication patterns, and community engagement approaches through systematic digital analysis observations and Instagram archives. The findings indicate that these communities have developed innovative ways of utilizing Instagram features to create meaningful interfaith dialogue, combining local wisdom with universal peace values. They use a variety of content formats, including educational infographics, personal storytelling, and interactive discussions to engage young viewers. Although these communities face challenges such as limited algorithms and resources, their adaptability shows the potential of digital platforms in fostering interfaith dialogue and peacebuilding. This research makes three important contributions: first, developing a comprehensive analytical framework for studying peace activism in the digital era; second, uncovering effective strategies for integrating local wisdom with digital activism; and third, offering a practical model for developing sustainable social media-based peace programs.